Pencegahan Pernikahan Dini, Remaja Di Desa Sumare Kecamatan Mamuju - Darwis, Raodatul Jannah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Early marriage is part of a social phenomenon that must be taken seriously because it greatly influences the lives of teenagers entering adulthood. The aim of PkM is to create conducive, child-friendly environmental conditions and collective awareness of all government components and village communities in fostering and maintaining the lives of teenagers. The method used in implementing this activity was conducting a location survey and coordinating with the local village government as well as identifying the problem of early marriage in Sumare village. The results achieved are the creation of awareness from each Lion village government institution and the community regarding the importance of preventing early marriage. The conclusion of this PkM is that early marriage is a marriage carried out under the age specified in the healthy marriage age according to the BKKBN, namely women who marry for the first time at the age of under 20 years and men under the age of 25 years at their first marriage. This determination relates to reproductive crimes. Early marriage in Sumare village occurs because of one's own and individual desires, because of cultural factors that have existed for a long time and the existence of values ​​in society in determining the appropriate age for marriage.